The Curious Case of Saloma’s Legacy: Documenting the Works of Biduan Negara - Ahmad Kamal, Basyah Sallehuddin; Abdul Walid, Ali; Muhammad Qawiem, Hamizan (Human Resource Management Academic Research Society, 2021)
Puan Sri Datin Amar Salmah Ismail, known professionally as Saloma, is Malaysia’s own Biduan Negara. Even though most people today recognised her as the significant other of Tan Sri Dato’ Amar (Dr) P. Ramlee, Saloma’s popularity as one of Malaysia’s prominent singers is undeniable. However, given her position as Biduan Negara of Malaysia, the documentation of her legacy has reflected anything but, and this article aims to explain the problems plaguing efforts to properly document Saloma’s legacy. The list of recordings has been incomplete for years, even though attempts were made to fortify her legacy by re-releasing her recordings after her demise. Her participation on television programmes and radio recordings were also not properly documented. Her vast collections of couture have been in the storage for almost 30 years, and only a handful of attires were exhibited to the public. At the same time, her handful of appearances on films are still accessible, even though some of her earlier films are unsalvageable. Serious efforts must be taken to properly document Saloma’s legacy, as Biduan Negara is not just an ordinary title for a singer who contributed so much to Malaysia’s arts.